RISK FACTORS OF LEPROSY IN DAHA HUSADA GENERAL HOSPITAL, KEDIRI CITY: Faktor Risiko Kejadian Kusta di Rumah Sakit Umum Daha Husada Kota Kediri - Syahirul Alim; Chatarina Umbul Wahyuni; Diah Indriani (Jurnal Berkala Epidemiologi, 2023)
Background: East Java Province is a province on the island of Java with a high incidence of leprosy. Daha Husada Kediri General Hospital is a hospital that provides health services to leprosy patients. Objective: To analyze the risk factors for leprosy in Daha Husada General Hospital, Kediri City. Methods: This study used a case-control research design to use an analytic observational method. The case group was patients diagnosed with leprosy and treated at Daha Husada General Hospital. In contrast, the control group was patients who were not diagnosed with leprosy and were treated at Daha Husada General Hospital. The variables used are age, education level, occupation, gender, and contact history. The number of respondents was 362 respondents divided into case and control groups, each of which was 181 people. Data collection is done through medical records. Results: The p-value for age 0.01<0.05 with OR 2.60 and 95% CI (1.64-4.14), the p-value for educational level (0.01)<0.05 with OR 2.99 and 95% CI (1.93-4.60), the p-value for sex (0.00)<0.05 with OR 0.43 and 95% CI (0.27-0.68), the p-value for history contact (0.01) <0.05 with OR 5.56 and 95% CI (2.51-12.31) which means that age, educational level, gender, contact history are related to leprosy. Conclusion: Age, education level, gender, and contact history determine the transmission of leprosy at Daha Husada General Hospital, Kediri.